2019
DOI: 10.1002/jlb.mr0519-143r
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic impacts of CSF1R deficiencies in humans and model organisms

Abstract: M proliferation, differentiation, and survival are controlled by signals from the M CSF receptor (CSF1R). Mono-allelic gain-of-function mutations in CSF1R in humans are associated with an autosomal-dominant leukodystrophy and bi-allelic loss-of-function mutations with recessive skeletal dysplasia, brain disorders, and developmental anomalies. Most of the phenotypes observed in these human disease states are also observed in mice and rats with loss-of-function mutations in Csf1r or in Csf1 encoding one of its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 162 publications
(478 reference statements)
7
115
0
Order By: Relevance
“…Knock-in reporters, for example in the Cx3Cr1 (38) and Ccr2 loci (39) have been widelyutilized in the study of macrophage biology, but in each case the endogenous gene is knocked out. Although heterozygous mutation of Csf1r has no overt phenotypic impact in mouse, rat or human, there is no dosage compensation (1). Given the central role of CSF1R in macrophage homeostasis, a knock-out insertion is undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…Knock-in reporters, for example in the Cx3Cr1 (38) and Ccr2 loci (39) have been widelyutilized in the study of macrophage biology, but in each case the endogenous gene is knocked out. Although heterozygous mutation of Csf1r has no overt phenotypic impact in mouse, rat or human, there is no dosage compensation (1). Given the central role of CSF1R in macrophage homeostasis, a knock-out insertion is undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the broader impact of this approach on the innate immune system remains unclear. CSF1R is expressed by cells of the myeloid lineage 14 and therefore it is anticipated that the inhibition of CSF1R would not only affect microglia, but also have potential on-target effects in circulating and tissueresident myeloid populations, with a possible downstream immunosuppressive effect. CSF1R can be activated by two independent ligands with high affinity, the colony stimulating factor 1 (CSF-1) 15 and the recently identified interleukin 34 (IL-34) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…6). Our study yields a number of 239 important observations that could only be revealed by multi-dimensional imaging using a tamoxifen-240 independent, cell type-specific fluorescent reporter model(Hume et al, 2019b(Hume et al, , 2019a. Firstly, in 241 contrast to previous reports (Gouon-Evans et al,2000, 2002), we demonstrate that Mφs encase the 242 length of elongating TEBs and are not restricted to the TEB neck.…”
mentioning
confidence: 60%